Role of arginase in asthma: potential clinical applications. Issue 1 (January 2010) - Munder, Markus
Allergic asthma is a chronic disease with significant morbidity and mortality. It affects 300 million people worldwide and absorbs a significant amount of the healthcare budget. The predisposition to asthma is dictated by complex genetic regulation, and the asthmatic inflammation itself is characterized by the interplay of various local cells of the bronchial tree and invading inflammatory immune cells. The clinical problems of asthma are owing to intermittent airway hyper-responsiveness that can become chronic in the course of the disease. Histopathologically, infiltration with a variety of inflammatory cells, smooth muscle cell hyperplasia and hypertrophy, goblet cell hyperplasia and subepithelial fibrosis are found in asthmatic inflammatory tissue. This special report sets out to review data on the role of the enzyme arginase andL -arginine metabolism as a unifying element of asthma pathophysiology and as a potential target for future clinical asthma treatment.